The Malays: Pathfinders and Trailblazers - Mohamad Hazizie Sulkafle, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2022)
Launched on 11th June 2022 by His Royal Highness the Sultan of Perak Darul Ridzuan, Sultan Dr. Nazrin Muizzuddin Shah, this book indeed had brought a new perspective in understanding the Malay history, culture, and civilization. The launching of this book took place not long before the premier screening of Mat Kilau, a box-office film in Malaysia which recently had achieved an unprecedented collection of almost RM100 million (as of 13th September 2022). Although these two phenomena were not directly related, yet the publication of this book and the outburst of Mat Kilau film may be seen as part of the recently growing consciousness among the Malays regarding their identity, history, culture, and civilization. The author himself, for example, stated in his Introduction “Malays are at the crossroads. Is there hope for the Malays to find the way out of these self-inflicting mortal wounds?”. Hence, using history as the reference, the author hoped to present the answer to that question to the Malay people.